Marketing innovation and sustainable competitive advantage of manufacturing SMEs in Ghana - Quaye, D.; Mensah, I. (Management Decision, 2018)
Purpose – The purpose of this paper is to establish how small- and medium-sized enterprises (SMEs) in water, beverage, soap, detergent, metal fabrication, wood and furniture manufacturing industries can sustain or improve their competitive advantage by integrating specific resources and capabilities. The paper seeks to offer an alternative framework “resource capability-based view (RCBV)” that provides a strategic marketing direction for SMEs regarding how innovative marketing practices and dynamic marketing capabilities integrate to create sustainable market advantage. Design/methodology/approach – This current paper employed a quantitative survey design with a positivist methodological research paradigm. The paper used a multi-stage stratified and simple random sampling technique to collect data from 591 manufacturing SMEs in Ghana. SMEs in water, beverage, soap, detergent, metal fabrication, wood and furniture manufacturing industries were sampled for the study. A structural equation model was employed to test the study hypotheses to arrive at the findings. Findings – The study found that product design and packaging innovations, promotion innovations, retail innovations and pricing innovations provide sustainable market advantage for water, beverage, detergent and metal fabrication SMEs. The paper also found that new product designs and packages are the major drivers of sustainable market advantage followed by innovative retail outlets. The paper further originated that integrating marketing competence (marketing resources and marketing capabilities) and innovative marketing activities provides a marginal improvement in competitive advantage. Physical resources may result in market advantage but integrating physical resources with dynamic marketing capabilities provides sufficient competitive sustainability in a competitive market. Practical implications – SMEs in water, beverage, soap, detergent, metal fabrication, wood and furniture manufacturing industries should prioritise their key marketing resources and capabilities in product designs, promotion, pricing and retailing innovations in order to sustain market advantage. Old products should not be faded from the market but rather SME managers should employ innovative retail strategies, such as eco-friendly advertising, product re-branding and digital platforms (social network sites and websites), which are important to sustaining market performance. Government must develop targeted policies to bridge the information gap between SMEs and research institutions such as universities through regular subsidised entrepreneurial training and creation of semi-annual industry-academic fairs. The main theoretical contribution of this current paper is the development of “RCBV” as a framework which shows how SMEs can integrate specific resources and capabilities to achieve sustainable market advantage. This framework offers an integrative view of conventional resource-based view and dynamic capability theory (DCT) which are independently examined in the literature. Originality/value – This current study has proposed an integrated and elaborative approach to the conventional resource-based view and DCT which does not provide a composite understanding in the literature. SMEs may lack the needed resources and capabilities to introduce new products or extant product lines but this paper has demonstrated that how SME can sustain market advantage of existing product(s) by synchronously using specific marketing resources and capabilities. The proposed framework offers a guide for SMEs to integrate their physical resources and capabilities to sustain their market advantage.
Keywords: Competitive advantage; Innovation; Manufacturing; Marketing; Marketing capabilities; Sustainability